Kontribusi LAZISMU dalam Mendukung Kesejahteraan Ekspatriat Indonesia melalui Program Khidmat di Arab Saudi: LAZISMU's Contribution in Supporting the Well-Being of Indonesian Expatriates through the Khidmat Program in Saudi Arabia - Khaerul Aqbar; Muhammad Musyawir K. (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
Indonesian expatriates residing in Saudi Arabia often face challenges in meeting basic needs and performing religious obligations in their new environment. This research explores the contribution of the Muhammadiyah Amil Zakat Infaq and Shadaqah Institute (LAZISMU) Saudi Arabia in supporting the well-being of Indonesian expatriates through the Khidmat program. Adopting a participatory approach, this study identifies the needs of Indonesian expatriates and the programs implemented by LAZISMU to address those needs. The findings reveal that LAZISMU Saudi Arabia plays a crucial role in providing assistance to those in need, particularly Indonesian expatriates, students, and Muhammadiyah members. The Khidmat programs implemented include zakat fitrah services, food package distribution, iftar meal sharing, and breaking of the fast gatherings. These programs have a positive impact in meeting the basic needs of Indonesian expatriates and strengthening social bonds and solidarity among the Muslim community. The effectiveness of the programs is supported by a partnership with the Indonesian Consulate General, enabling targeted identification and distribution of aid. This research contributes to understanding the role of Islamic philanthropic organizations in supporting the well-being of the Indonesian expatriate community in Saudi Arabia and provides recommendations for developing more effective programs in the future.